HUBUNGAN MALAYSIA DENGAN KOREA UTARA PASCA TERJADI PEMBUNUHAN TERHADAP KIM JONG-NAM - Atri Yanda Afdali Hetri; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This writing is a picture of relationship between Malaysia and North Korea after the death case of Kim Jong-nam who is the current North Korea’s step brother, Kim Jong-un. The different point of view of that death case make the problem of the diplomatic of those countries.This research in teoritically use realism that is supported by the foreign legacy that is set the relationship between the countries. The formulas of arguments, datas, facts, and teoritical framework in the research, use qualitative method. This research also uses nation-state as the analysis layers. The return of ambassador of two countries show the Kim Jong-nam’s death case bring the effect to the two countries. The relationship that started really well turn into a conflict all of a sudden.Keywords : Death Case, Ambassador, Diplomatic, Malaysia, North Korea